Study on macrophytes in Ramala lake, Dist. Chandrapur (M.S.) - P.J. Khinchi; P. M. Telkhade; N.R. Dahegaonkar; S. B. Zade (Environment Conservation Journal, 2008)
The present piece of  investigation  deals  with  aquatic  Macrophytes  of  Ramala  Lake,  Dist.  Chandrapur, Maharashtra during the period May-2006 to April-2007. The lake is in the heart  of city receiving sewage  from maximum  part  of  city  through  Mucchi  Nala.  During  the  study   period,   total   of   18   species   representing families  of  aquatic  macrophytes.  Among  these,  species  Eichhornia     and  Pistia  shows  their  dominance,  indi- cating highly eutrophic condition  of lake.